Vegetation Analysis of Tree Species in the Hungayono Karst Ecosystem - Ishak, Rafli; Katili, Abubakar Sidik; Husain, Ilyas H.; Mamu, Hartono D.; Kandowangko, Novri Youla (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Karst ecosystems possess distinctive edaphic and hydrological characteristics that influence vegetation structure, yet information regarding tree vegetation in the Hungayono karst area remains limited. This study aimed to analyze species composition, vegetation structure, and community patterns of tree vegetation in the Hungayono Karst Ecosystem, Tulabolo Pinogu Resort, Bogani Nani Wartabone National Park. A survey method with purposive sampling was applied at three karst topographic zones representing the lower, middle, and upper areas. Five 20 × 20 m plots were established at each zone, resulting in 15 observation plots. Vegetation data were analyzed using density, frequency, dominance, Important Value Index (IVI), and Principal Component Analysis (PCA). The results recorded 12 species with a total of 61 individuals belonging to the divisions Tracheophyta and Pinophyta. The lower karst zone exhibited the highest species richness and abundance, whereas the upper zone showed a simple and nearly monodominant community structure. Bambusa multiplex dominated Point I with an IVI of 76.38%, Neolamarckia macrophylla dominated Point II with an IVI of 179.5%, and Neolamarckia cadamba dominated Point III with an IVI of 300%. PCA analysis indicated heterogeneous vegetation communities influenced by topography, soil thickness, and microclimatic conditions. These findings highlight the ecological role of karst topographic gradients in shaping tree vegetation structure and provide scientific information for karst habitat management and conservation.